Application of fractional order theory of thermoelasticity in an elliptical disk and associated thermal stresses - Thakare, Shivcharan; Panke, Y.; Hadke, K. (Zielona Góra: Uniwersytet Zielonogórski)
In this article, a time fractional-order theory of thermoelasticity is applied to an isotropic homogeneous elliptical disk. The lower and upper surfaces of the disk are maintained at zero temperature, whereas the sectional heat supply is applied on the outer curved surface. Thermal deflection and associated thermal stresses are obtained in terms of Mathieu function of the first kind of order 2n. Numerical evaluation is carried out for the temperature distribution, Thermal deflection and thermal stresses and results of the resulting quantities are depicted graphically.
Keywords: elliptical disk; fractional-order theory; Caputo derivative; integral transform; thermal stresses; thermal deflection